An Update of Male Contraception: A Review of Cellular Perspective - Silvia W Lestari (Journal of Global Pharma Technology, 2016)
Introduction: Similar to the world, Indonesia also undergoes a population explosion. One solution to overcome this population problem is to conduct contraception. Although woman contraception is widely used, still the role of man is needed. There are a few methods in male contraception, but all is still not proven optimally. Therefore, it is intend to understand more about the cellular mechanism of male contraception. Methods: A computerized finding process of database in Pub med which related to the key words was performed for obtaining data. After that, the most update and relevant articles were reviewed and selected. Results: The results are mainly revealing the regimens that are administered in male hormonal contraception and substances that are used in immunocontraception. Furthermore, this reviews also reveales the cellular mechanism of both types of male contraception. In male hormonal contraception, the mechanism was depends on negative feedback in hypothalamic-pituitary-gonadal axis by regimens to impair the spermatogenesis into severe-oligozoospermia or azoospermia. In addition, immunocontraception was based on ‘vaccination’ concept in which antibodies recognize proteins in the spermatozoa as